The Educational Role of School Principals in Improving the Quality and Productivity of Quality Management in Darussalam Private Middle Schools, Medan - Oktapia, Dina; Sibarani, Lola Amalia; Widya Maulida, Khansa Arista; Sirait, Fauzan Azhima; Akmalia, Rizki (JUPE : Jurnal Pendidikan Mandala, 2023)
Role is a dynamic aspect of position (status) if a person performs his rights and obligations according to his position then he has carried out a role. The principal as a policy maker in schools functions optimally and is able to lead schools wisely and with direction and leads to the achievement of maximum goals in order to improve the quality and quality of education in schools. This study aims to study and describe the role of school principals in improving education management in Darussalam Middle School. The research method used in this study is descriptive qualitative research using observation techniques and also interviews with the principal of the research location. The results obtained explained that the principal had made various efforts and had improved to support the management of education in  Darussalam Middle School Efforts made related to the important role in terms of leadership and management of madrasas both for teachers, students, facilities and other school supporters. The conclusion in this study is that the role of the principal is very important in improving education management and the role of the principal must be carried out in the role of educators, managers, administrators, supervisors, leaders, innovators and motivators.